Melhor Estimativa da Posição de um Ponto Emissor no Espaço M-Dimensional e Determinação dos Dominios Ótimos de Busca DOI: 10.14209/jcis.1992.3 - Baczynski, Jack (Journal of Communication and Information Systems, 2015)
The best estimate of the position of an emitting point located in the m-dimensional space and conditional to the observation of the emitting point’s propagation trajectories - added to gaussian distortion, is obtained. The analytical and matrix form solution developed is based on the implementation of the Maximum Likelihood Hypotesis Testing as one considers a continous m-dimensional field of hipotesis. Refering to the position of the emitting point in the m-dimensional space, gaussian conditional probability densities are derived. The optimum detection/search domains are also implemented, as junctions of the required probabilities (P) of detection or success. The results directly apply to the radio direction finding problem, electronic support measures (ESM) problem and search for submersed emitting objects.